2001
DOI: 10.3168/jds.s0022-0302(01)74604-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Source and Soluble Carbohydrate Addition on Rumen Fermentation and Lactation Performance of Holstein Cows

Abstract: Rumen in vitro and in vivo experiments were conducted to evaluate the effect of rumen undegradable protein and soluble carbohydrates on rumen ammonia N release and lactation performance of Holstein cows. In the in vitro experiment, freeze-dried annual ryegrass (Lolium multiflorum, LAM) pasture was supplemented 1:1 with ground corn-based grain supplements containing expeller or solvent soybean meal with sucrose or lactose supplements at 0, 2.5, or 5% of dry matter (DM). The ammonia release rate was slower with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 29 publications
6
38
1
4
Order By: Relevance
“…Due to the rapid fermentation of sugars relative to the other carbohydrate fractions, rumen pH is expected to be lower for diets containing sugars. Many studies in the literature have shown that rumen pH is not affected when dietary starch sources are partly replaced by sucrose (Stensig et al, 1998;Khezri et al, 2009;McCormick et al, 2001) or lactose (DeFrain et al, 2004). Contrary to results of Penner and Oba (2009), we observed tendencies for decreased ruminal pH in goats fed SU compared with those fed CON.…”
Section: Ruminal Fermentation and Blood Metabolitescontrasting
confidence: 99%
See 1 more Smart Citation
“…Due to the rapid fermentation of sugars relative to the other carbohydrate fractions, rumen pH is expected to be lower for diets containing sugars. Many studies in the literature have shown that rumen pH is not affected when dietary starch sources are partly replaced by sucrose (Stensig et al, 1998;Khezri et al, 2009;McCormick et al, 2001) or lactose (DeFrain et al, 2004). Contrary to results of Penner and Oba (2009), we observed tendencies for decreased ruminal pH in goats fed SU compared with those fed CON.…”
Section: Ruminal Fermentation and Blood Metabolitescontrasting
confidence: 99%
“…Sucrose had no significant effect on DMI in dairy goats (Table 3). Even though some researchers reported that DMI was not affected by supplementation with sucrose (McCormick et al, 2001;, there is no report in the literature exhibiting negative effects on DMI of feeding sugar. In contrast, Broderick et al (2008) reported that DMI increased linearly as sucrose supplementation (sucrose vs. corn starch) increased to 7.5% of dietary DM.…”
Section: Dm Intake and Milk Production And Compositionmentioning
confidence: 94%
“…Chen et al (2002) also identified urea reduction in the plasma of high production dairy cows when given heat-treated soy, as compared to feeding soy grouts and protected fat. McCormick et al (2001) describes the reduction of plasmatic urea levels in dairy cows given feed rations containing a high percentage of protected protein (6.8% vs. 5.8% vs. 5%).…”
Section: Nitrogen Metabolismmentioning
confidence: 99%
“…Feed that contain high non-structural carbohydrates in the rumen to stimulate the growth of lactobacilli bacteria and rumen fluid pH will lead to lower down, as presented by McCormick et al (2001) who stated that ruminants fed a lot of structural carbohydrates (fiber) will result in rumen fluid pH tends to move towards 7.5, whereas if fed with soluble carbohydrate rumen fluid pH will bring will move toward 5.0. Thus it can be ascertained that the difference in pH values between CF 0 and CF 3 is closely related to differences in composition chemical or digestible carbohydrate content between the feed is tested in goat.…”
Section: Resultsmentioning
confidence: 99%